Yield and quality of hybrid sunflower (Helianthus annuus) as affected by irrigation and fertilization - ALIPATRA, A; BANERJEE, H; BHATTACHARYYA, K; BANDOPADHYAY, P; RAY, K (The Indian Journal of Agricultural Sciences, 2019)
Present study was carried out to evaluate the effects of varying levels of irrigation and fertilizers, as well as their interaction on the yield, oil quality and nutrient uptake by hybrid sunflower (Helianthus annuus L.) (cv. Aditya) at farmer’s field, Nadia, West Bengal. Results revealed that average seed yield, stalk yield, oil percentage and oil yield of Aditya was the highest with three irrigations. These parameters were also significantly and synergistically increased by the application of N80P40K40B1.5S25.The values of linoleic acid and oleic acid concentrations were greatest in seeds obtained with N80P40K40B1.5S25 under single irrigation and double irrigations, respectively. In contrary, the proportions of palmitic acid and stearic acid were lowest with same fertilizer management practices under three irrigations and single irrigation, respectively. The lowest saponification value and maximum iodine value of sunflower oil was obtained with N80P40K40B1.5S25 under single irrigation and three irrigations, respectively.The increase in irrigation frequency from one to three brought about significant increase in nutrient uptake by tested cultivar. Total N and S uptake was significantly higher when the tested cultivar grown with N80P40K40B1.5S25; however, total P and K uptake was higher with N80P40K40S25. Application of N80P40K40B1.5 exerted higher boron (B) uptake. Thus fertilization with RDF (80 kg N, 40 kg P2O5 and 40 kg K2O/ha) in combination with 1.5 kg B and 25 kg S/ha under controlled irrigation at 30,60 and 80 DAS can be used to sustain hybrid sunflower production during winter in West Bengal.